2022
DOI: 10.3389/fped.2022.761265
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Disseminated Mycobacterium intracellulare Infection With More Than 1-Year Follow-Up in a Young Boy With IFNGR1 Deficiency

Abstract: All members of the genus Mycobacterium are collectively labeled as “non-tuberculous mycobacterium” (NTM), with the exception of the Mycobacterium tuberculosis complex and M. leprae. Recently, the incidence of NTM infection and number of cases have been increasing, but their identification remains difficult in some countries. Usually, NTM infections and diseases are associated with primary immunodeficiency diseases (PIDs), and their prognoses can be improved with a timely diagnosis and appropriate treatment. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[6][7][8][9][10] A recent case reported that a diffuse NTM disease caused by Mycobacterium intracellulare occurred in a child with IFNGR1 deficiency, with a good prognosis after antimycobacterial treatment. [11] A patient diagnosed with septic arthritis was due to NTM infection as Mycobacterium intracellulare was isolated by culture and showed an excellent prognosis with antimycobacterial treatment. [12] This study shows that the clinical application of molecular diagnostic technology plays a crucial role in diagnosing nontuberculous mycobacteriosis and the differential diagnosis with other inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10] A recent case reported that a diffuse NTM disease caused by Mycobacterium intracellulare occurred in a child with IFNGR1 deficiency, with a good prognosis after antimycobacterial treatment. [11] A patient diagnosed with septic arthritis was due to NTM infection as Mycobacterium intracellulare was isolated by culture and showed an excellent prognosis with antimycobacterial treatment. [12] This study shows that the clinical application of molecular diagnostic technology plays a crucial role in diagnosing nontuberculous mycobacteriosis and the differential diagnosis with other inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%
“…[6–10] A recent case reported that a diffuse NTM disease caused by Mycobacterium intracellulare occurred in a child with IFNGR1 deficiency, with a good prognosis after antimycobacterial treatment. [11] A patient diagnosed with septic arthritis was due to NTM infection as Mycobacterium intracellulare was isolated by culture and showed an excellent prognosis with antimycobacterial treatment. [12]…”
Section: Discussionmentioning
confidence: 99%
“…These deficiencies include autosomal recessive and autosomal dominant disorders, complete, and partial functional defects, forms in which the surface receptors are dysfunctional, forms in which the surface receptors are absent, and other mechanisms disrupting the function of the IFN-γ receptors. STAT1, JAK1, and gp91 phox deficiencies also impair cellular responses to IFN-γ [ 19 ].…”
Section: Discussionmentioning
confidence: 99%